Sirkulasi Keputusan Dan Dampak Menjadi Pekerja Migran: Studi Etnografi Proses Pengambilan Keputusan Menjadi Pekerja Migran Indonesia - Citra Nur Hamidah (Jurnal Ketenagakerjaan, 2018)
Limited employment opportunities in Indonesia encourage Indonesians to seek employment abroad and choose to become migrant workers. There are two migration processes; procedural migration and unprocedural migration. In this study, I would like to show the global labor migration reviewed from the local level of the migrant worker’s village. My focus to explore the decision-making process of migrant workers created in thehousehold and the village. I argue that ethnography approach casting light on social and cultural contexts for thought, reason, and action can explain how choices are framed and constituted. I used an ethnography approach to explain the decision-making process and to understand the daily life of migrant workers in the village and household units. I conducted fieldwork (live in) in Kebondalem Village, Banyuwangi for 3 months.In the context of migrant workers, I offered a new concept to explore the decision-making process, that is 'long distance decision making process'. The process of decision making into migrant workers is never completed and always formed through daily activities, even households negotiated.